Pembentukan Karakter Siswa Melalui Ungkapan Hadih Maja Di Sekolah Menengah Pertama Se-Kecamatan Samudera Kabupaten Aceh Utara - Bahri, Saiful; Fauzan, Fauzan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
The process of character building by focusing on the use of hadih maja expressions with the aim that the younger generation is able to master the Indatu language which has been eroded by the times and is even now slowly disappearing, so from this explanation what we want to find out. maja at Junior High School in Samudera District, North Aceh Regency. To get the results of the study, the researcher used a qualitative research type with a descriptive approach. From the explanation that the authors get from the results of the study, it shows that in an effort to build the character of Islamic Religious Education teacher students at SMP Kecemat Samudra, the researchers have not shown the expectations of the researchers, the average teacher never uses Maja's expression in coaching. The process of forming student character, even unfortunately many teachers do not understand the gift. so on this basis it must be learned by the teacher so that this language is not lost in time